(untitled) (Research, Society and Development, 2020)
Fieldwork is important to unveil environmental issues and, above all, to explore the content given in the classroom in a more dynamic and practical way, given this approach, it aims to analyze the benefits of using fieldwork as a methodological tool for the teaching. This research resulted in the pedagogical practice adopted at the Municipal School Profª Maria Eulália Vieira, in the discipline of Geography, having water as its starting point and its importance for the residents of the municipality of Três Lagoas-MS. In the place there is a stream that had to be plumbed because of the urbanization process that took place in the city. The focus was to clarify the 8th year students about the environmental issue, including the parameters of the municipal public policies, therefore, a didactic sequence was used. At first, he presented a video about São Paulo, “Entre Rios”; in the continuation, the students applied questionnaires to the residents of the Jardim Alvitrados neighborhood, where frequent flooding occurs. Then, a field trip was held with the students to show where the Onça stream flows. Finally, with the interaction of the students and analysis of the questionnaires and photographic images, one can understand the main environmental problems in the neighborhood, it is clear that there has been significant progress in the way they understand the importance of water and its influence / relationship with the environment.